Generation of neutralizing antibodies and divergence of SIVmac239 in cynomolgus macaques following short-term early antiretroviral therapy. - Ozkaya Sahin, G; Bowles, E; Parker, J; Uchtenhagen, H; Sheik-Khalil, E; Taylor, S; Pybus, O; Mäkitalo, B; Walther-Jallow, L; Spångberg, M; Thorstensson, R; Achour, A; et al. (Public Library of Science, 2010)
Neutralizing antibodies (NAb) able to react to heterologous viruses are generated during natural HIV-1 infection in some individuals. Further knowledge is required in order to understand the factors contributing to induction of cross-reactive NAb responses. Here a well-established model of experimental pathogenic infection in cynomolgus macaques, which reproduces long-lasting HIV-1 infection, was used to study the NAb response as well as the viral evolution of the highly neutralization-resistant SIVmac239. Twelve animals were infected intravenously with SIVmac239. Antiretroviral therapy (ART) was initiated ten days post-inoculation and administered daily for four months. Viral load, CD4(+) T-cell counts, total IgG levels, and breadth as well as strength of NAb in plasma were compared simultaneously over 14 months. In addition, envs from plasma samples were sequenced at three time points in all animals in order to assess viral evolution. We report here that seven of the 12 animals controlled viremia to below 10(4) copies/ml of plasma after discontinuation of ART and that this control was associated with a low level of evolutionary divergence. Macaques that controlled viral load developed broader NAb responses early on. Furthermore, escape mutations, such as V67M and R751G, were identified in virus sequenced from all animals with uncontrolled viremia. Bayesian estimation of ancestral population genetic diversity (PGD) showed an increase in this value in non-controlling or transient-controlling animals during the first 5.5 months of infection, in contrast to virus-controlling animals. Similarly, non- or transient controllers displayed more positively-selected amino-acid substitutions. An early increase in PGD, resulting in the generation of positively-selected amino-acid substitutions, greater divergence and relative high viral load after ART withdrawal, may have contributed to the generation of potent NAb in several animals after SIVmac239 infection. However, early broad NAb responses correlated with relatively preserved CD4(+) T-cell numbers, low viral load and limited viral divergence.